ANALISIS PROSES PEMBELAJARAN MATEMATIKA DI SMK RSBI SURAKARTA - Puspitasari, Norma; Sujadi, Imam; Soeyono, Soeyono (Journal of Mathematics and Mathematics Education, 2012)
Abstract This study aims :1)to describe process of learning mathematics in vocational RSBI Surakarta.2) to know whether the process of learning mathematics in vocational RSBI Surakarta whether it is in accordance with quality assurance system RSBI.This study used a qualitative approach. The subject of this study was a mathematics teacher in class XI program of tourism expertise. The data was taken by RPP and learning activities in the transformation geometry subject. Instruments used observation and interview guide sheet. Techniques of data collection by interview, observation and documentation. The validity of the data used the triangulation  methods and data sources. Data analysis techniques included data reduction, data presentation and conclusions.These results indicated that: 1) The process of learning mathematics at SMK Negeri 6 Surakarta were as follows (a) The planning was not appropriate  with the standards process because there are some errors in the writing of the identity,  programming skills are not included the amount of meetings and the planning has not been made  (b) The implementation of  mathematics learning  in the transformation geometry subject in early learning activities, the teacher of grade XI mathematics SMK Negeri 6 Surakarta apperception conducted a glimpse for repeating previous material. The main activities of learning, classroom math teacher of SMK Negeri 6 Surakarta XI UPW has implemented major exploration by encouraging students to do the experiment in determining the reflection point and the point of rotation with Geogebra software media, teachers conducted elaboration by discussion and taking conclusion after demonstration done without giving opportunities for students to analyzit. The teacher conducted confirmation by giving positive feedback and reinforcement in verbal to the success of students, gave the confirmation to the result of exploration and elaboration and got correction to the student mistakes. (c) The use of information technology-based media on the powerpoint application program, animation or presentation media in the mathematics learning process was optimally supported by Geogebra media software as supported transformation geometry media. (d) Use the usual methods of teaching applied mathematics teacher SMK Negeri 6 Surakarta was demonstration because it considered suitable for the material submitted with the help of the above media. (e) The use of English in learning mathematics restricted for the opening only, the slides that used in the learning was also not in English. (F) In the end of the lesson the teacher give students chance to ask which part of the material that still not understand, Taking conclusion from the material together with the students, giving exercises, and post test. (g) In the assessment step, grade XI mathematics teacher of SMK Negeri 6 Surakarta correcting students' test results, give feedbacks and comments, restore the work to the students.The results of the research also showed that; 2) The process of mathematics learning at SMK Negeri 6 Surakarta if it has been related with quality assurance system are (a) The process of mathematics learning is good but not meet the standards process and has not been riched by learning process from one of developed OECD country or other developing country. (b) The process of learning in mathematic have developing a noble character, manners, noble, excellent personality, leadership, life enterpreneural, patriot and soul. (c) The use of English in mathematics teaching was too minimal only at the opening, the delivering materials also have not to use English. (d) The use of ICT have good proved by the learning process using the LCD and Geogebra software.Keywords: Mathematics Learning Process, Vocational RSBI,  Quality Assurance  System